Project BESPOKE (Integrated Bio-Behavioral Assessment of HIV and STI Among Young Tertiary Student Men Who Have Sex With Men in Nairobi, Kenya): A Respondent-Driven Sampling Survey Protocol - Mwaniki, Samuel Waweru; Mugo, Peter Mwangi; Palanee-Phillips, Thesla (Frontiers in Public Health, 2021)
Introduction: Globally, men who have sex with men (MSM) are a key population for the HIV epidemic. Among MSM, young MSM (YMSM) are disproportionately affected by HIV and other sexually transmitted infections (STI). However, there is a dearth of research and interventions targeting HIV/STI prevention among YMSM. In Kenya, there is paucity of knowledge on the burden of HIV/STI and related factors among YMSM, including tertiary student MSM (TSMSM). The barriers TSMSM experience in accessing and utilizing health services in their learning institutions have been seldom explored. In the context of healthcare providers (HCP) working in tertiary institutions, little is known about their knowledge, attitudes and practices towards providing services to TSMSM. Methods: The aims of the study are to: estimate prevalence and correlates of HIV/STI among TSMSM; explore experiences of TSMSM with access and utilization of health services; and assess HCP knowledge, attitudes and practices towards provision of services to TSMSM. A mixed-methods approach will be used in three phases: Phase I – formative qualitative research will be conducted to understand TSMSM social networks, select ‘seeds’ and explore strategies for implementing a respondent-driven sampling (RDS) survey. Interviews will be conducted with at least three staff who work in community based/non-governmental organizations that serve MSM and at least 10 TSMSM. Phase II – an integrated bio-behavioral assessment (IBBA) with population size estimation (PSE) will be conducted, where 200 TSMSM recruited by RDS will be offered HIV/STI testing, complete a behavioral survey and provide information for PSE. Phase III – in-depth interviews will be held with 20 TSMSM selected from 200 TSMSM in phase II, to explore their experiences with access and utilization of healthcare services. Focus group discussions will be conducted with HCP working in tertiary institutions to assess their knowledge, attitudes and practices towards providing services to TSMSM. Data collection started in September 2020 and is expected to end by September 2021. Discussion: Findings from this study will be useful in informing HIV/STI prevention programming for TSMSM, by policy makers such the Kenyan ministries of health and education, tertiary education institutions, service providers, advocacy groups and other interested stakeholders.